Analisis Kemandirian Belajar Peserta Didik SMP Melalui Implementasi LKPD Discovery Learning Berbantuan Augmented Reality - Ani Nurhidayanti*; Erfin Nofianti; Heru Kuswanto; Insih Wilujeng; Suyanta Suyanta (Universitas Syiah Kuala, 2022)
Learning has now gradually recovered from the effects of the COVID-19 pandemic with the start of limited face-to-face learning. This makes educators need to innovate so that students still have independent learning. Online learning that is less than optimal causes students to be too passive when learning offline. The use of technology, the selection of interesting learning models, and media according to the characteristics of the material, especially abstract material, are still needed to answer the challenges of 21st-century learning. The use of technology and the development of students' learning independence is very important to face real life and make learning more effective. The purpose of this study is to analyze the learning independence of students through the implementation of LKPD discovery learning assisted by augmented reality. This research is descriptive qualitative research with 28 students of class VIII at SMP N 2 Karangnongko. The data collection technique used a student learning independence questionnaire, which was triangulated with learning observation sheets and interviews with science teachers. The data analysis technique according to Miles Huberman (1992) goes through three steps, namely data reduction, data displaying, and conclusion drawing/verification. The results of the learning independence questionnaire were analyzed using the percentage technique. Based on the learning independence questionnaire data, the average percentage is 70% in the medium category